Diazotroph Diversity and Nitrogen Fixation in Summer Active Perennial Grasses in a Mediterranean Region Agricultural Soil - Gupta, Vadakattu V. S. R.; Zhang, Bangzhou; Penton, Christopher Ryan; Yu, Julian; Tiedje, James M. (Frontiers in Molecular Biosciences, 2019)
Summer-growing perennial grasses such as Panicum coloratum L. cv. Bambatsi (Bambatsi panic), Chloris gayana Kunth cv. Katambora (Rhodes grass) and Digitaria eriantha Steud. cv. Premier (Premier digit grass) growing in the poor fertility sandy soils in the Mediterranean regions of southern Australia and Western Australia mainly depend upon soil N and biological N inputs through diazotrophic (free living or associative) N fixation. We investigated the community composition and diversity (nifH-amplicon sequencing), abundance (qPCR) and functional capacity (15N incubation assay) of the endophytic diazotrophic community in the below and above ground plant parts of field grown and unfertilized grasses. Results showed a diverse and abundant diazotrophic community inside plant both above and below-ground and there was a distinct diazotrophic assemblage in the different plant parts in all the three grasses. But there was a limited difference in the diversity between leaves, stems and shoots except that Panicum grass roots harboured greater species richness. Nitrogen fixation potentials ranged between 0.24-5.9 mg N kg-1 day-1 and N fixation capacity was found in both the above and below ground plant parts. Results confirmed previous reports of plant species-based variation and that Alphaproteobacteria were the dominant group of nifH-harbouring taxa both in the belowground and aboveground parts of the three grass species. Results also showed a well-structured nifH-harboring community in all plant parts, the first report of this type for a functional endophytic community. Overall, the variation in the number and identity of module hubs and connectors among the different plant parts suggests that co-occurrence patterns within the nifH-harboring community are compartmentalized and local environments of the niches within each plant part may dictate the overall composition of diazotrophs within a plant.